Characteristics of diarrheagenic Escherichia coli among patients with acute diarrhea in China, 2009‒2018. Issue 4 (October 2021) - Zhou, Shi-Xia; Wang, Li-Ping; Liu, Meng-Yang; Zhang, Hai-Yang; Lu, Qing-Bin; Shi, Lu-Sha; Ren, Xiang; Wang, Yi-Fei; Lin, Sheng-Hong; Zhang, Cui-Hong; Geng, Meng-Jie; Zhang, Xiao-Ai; et al.
Highlights: The burden of diarrhea attributed to diarrheagenic Escherichia coli (DEC) in China was high and increasing from 2009 to 2018, especially for three most frequent pathotypes including enteroaggregative E. coli (EAEC), enteropathogenic E. coli (EPEC), and enterotoxigenic E. coli (ETEC). Age profile of DEC prevalence and the pathotype composition was disclosed, which can help planning and adopting targeted preventive measures and antimicrobial therapy. Regional difference between urban and rural areas were identified for the five DEC pathotypes in acute diarrheal patients. Abstract: Objectives To investigate the epidemiological features of diarrheagenic Escherichia coli (DEC) in patients with acute diarrhea in China. Methods An active sentinel surveillance was performed in all-age patients with acute diarrhea in China, 2009‒2018. DEC was isolated and identified by serological assay and PCR from stool samples. Results DEC was determined in 6.68% (6, 119/91, 651) of the patients, with higher positive rates among females than among males (6.97% vs. 6.46%) and among 18‒59 years patients (7.88%) than among other age groups. Five pathotypes were identified, the most prevalent was enteroaggregative E. coli (EAEC), followed by enteropathogenic E. coli (EPEC), and enterotoxigenic E. coli (ETEC). Pediatric patients <5 years had higher positive rate of EAEC (2.07%), followed by EPEC (1.81%), and enterohemorrhagic E. coli (EHEC) (0.31%), while the 18‒59 years patients had higher infection of ETEC (2.36%). ETEC and EPEC were more frequently identified in urban than rural areas, with age and gender adjusted positive rate of 1.68% vs. 1.14% respectively, and 1.77% vs. 1.55%, while EIEC and EHEC were more frequently identified in rural areas. Conclusions These findings highlight the epidemiology features of DEC and underscores the need for conducting DEC surveillance.